Disruption management framework, models and applications - Yu, Gang (World Scientific Pub. Co., 2004)
This pioneering book addresses the latest research findings and application results on disruption management, which is the study of how to dynamically recover a predetermined operational plan when various disruptions prevent the original plan from being executed smoothly. A disruption management system will help decision-makers respond to disruptive events in real time so that the cost incurred by the disruption is reduced to a minimum. The impact of such systems is significant. For example, each year the disruption management system for US airlines generates savings of tens of millions of dollars
Keywords: Risk management; Decision making; Uncertainty